A deformation model of pulsating brain tissue for neurosurgery simulation. (May 2022) - Ying, Huasen; Liu, Peter X.; Hou, Wenguo
Highlights: A finite element model incorporating intracranial pressure. Calculate the deformation of brain tissue with an implicit Euler method. A circuit model of intracranial pressure dynamics. The simulated brain tissues pulsate with a rhythm. Abstract: Background and objectives: For neurological simulation, an accurate deformation model of brain tissue is of key importance for faithful visual feedback. Existing models, however, do not take into account intracranial pulsation, which degrades significantly the realism of visual feedback. Methods: In this paper, a finite element model incorporating intracranial pressure is proposed for simulating brain tissue deformation with pulsation. An implicit Euler method is developed to calculate the deformation of brain tissue. A circuit model of intracranial pressure dynamics is established based on cerebral blood and cerebrospinal fluid circulations. The intracranial pulsation of pressure is introduced into the deformation model, so that the simulated brain tissues pulsate with a rhythm in accord with the changes of intracranial pressure, which resembles real-life neurosurgery. Results and Conclusions: The experimental implementation of the proposed deformation model and the calculation method shows that it provides realistic simulation of brain tissue pulsation and real-time performance is achieved on an ordinary computer for certain procedures of neurosurgery.